Konstruksi Makna Ruqyah Syar’iyyah Bagi Pasien Gay - Naila Rahmi; Muhammad Firdaus; Ismandianto (Universitas Serang Raya, 2022)
Ruqyah syar’iyyah method for gay patient is one of interesting phenomenon that currently happening around society. This methods is still rare to be found, especially when it comes to treat patient that find their self as gay. Gay existency in Indonesia is still under debate among society. The contradiction created because of ruqyah syar’iyyah method that being told could help patient cured is creating another meaning for each patient itself. The purpose of this research is to understand patient motive, meaning of ruqyah syar’iyyah method for patient and the communication experience for patient. This study uses qualitative research method with phenomenology approach also uses snowball technique to get 4 informants as the subject of this research. Data collection done through in-depth interview, observation and documentation. Data analysis technique uses interactive data ana While for the data validation check, researcher uses triangulation and extension of participation method.The result of this study shown that first, the reason why gay patient doing ruqyah syar’iyyah method is split in two, there are past motive (because motives) (1) uncomfortable feelings (2) information from social media and (3) the willing to change, future motive (in order to motives) (1) self-intropection (2) getting close to god (3) having partner and heredity. Second, the meaning of ruqyah syar’iyyah for gay patient is Islamic law based, as a process of hijrah, and solution for variative disease. Third, the communication experience for patien is split in two which are happy and unhappy. Happy communication experience there are well accepted, getting new friends and getting peace. While for bad communication experience there are self-personal (feeling unwell), shunned by past friends, and getting underestimated